2015
DOI: 10.1016/j.bbmt.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Patients with Philadelphia-Positive Leukemia with BCR-ABL Kinase Mutations before Allogeneic Transplantation Predominantly Relapse with the Same Mutation

Abstract: Despite the successes of tyrosine kinase inhibitors (TKIs) in improving outcomes in patients with chronic myeloid leukemia (CML) and Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL), allogeneic hematopoietic stem cell transplantation (HSCT) continues to be an important and potentially curative option for selected patients with either disease. After HSCT, TKIs are increasingly being used to treat or prevent disease relapse, and practice patterns suggest that these TKIs are often chosen empirically w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Furthermore, it has been shown that persistence of very low levels of residual disease ( BCR-ABL1 < 0.1% IS ) detectable up to 10 years post-transplant has less implication for relapse [43]. It has been suggested that pre-transplant mutation analysis should be considered when selecting a TKI for post-transplant prophylaxis, based on the observation that the majority of resistant mutations are still detectable after transplantation and that patients often relapse with these mutant clones despite receiving TKI therapy [44, 45].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it has been shown that persistence of very low levels of residual disease ( BCR-ABL1 < 0.1% IS ) detectable up to 10 years post-transplant has less implication for relapse [43]. It has been suggested that pre-transplant mutation analysis should be considered when selecting a TKI for post-transplant prophylaxis, based on the observation that the majority of resistant mutations are still detectable after transplantation and that patients often relapse with these mutant clones despite receiving TKI therapy [44, 45].…”
Section: Resultsmentioning
confidence: 99%
“…An initial RT-PCR step with nested PCR was used to amplify exons 4 to 9 (codons 199 to 507) of the Abl kinase domain, and bidirectional Sanger sequencing of the PCR product was performed, as previously described 23 .…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there are data indicating that Ph‐positive ALL patients with detectable BCR‐ABL transcripts and kinase domain mutations before alloHSCT relapse after transplantation with the same mutation. Egan et al analyzed ABL kinase domain mutations in patients with CML and Ph‐positive ALL who had detectable BCR‐ABL transcripts before alloHSCT. Pretransplant ABL kinase domain mutations were found in 14 patients, including 4 patients with Ph‐positive ALL.…”
Section: Choice Of Tki For Posttransplant Maintenancementioning
confidence: 99%